68.6k views
2 votes
I'm not sure how to proceed with where I am on simplifying a fraction. I am trying to simplify the fraction 1 / (y / 5 - 1).

I'm not sure how to proceed with where I am on simplifying a fraction. I am trying-example-1

1 Answer

7 votes

We will simplify further as follows:


\begin{gathered} (1)/((y)/(5)-1)=(1)/((y-5)/(5))=((1)(5))/((1)(y-5)) \\ \\ =(5)/(y-5) \end{gathered}

***Sum of fractions***


(a)/(b)+(c)/(d)=(ad+bc)/(bd)

Now, using this with the information given we have:


\begin{gathered} (y)/(5)-1=(y)/(5)-(1)/(1)=((y)(1)-(5)(1))/((5)(1)) \\ \\ =(y-5)/(5) \end{gathered}

Now, we know that this expression was the denominator of 1, so:


(1)/((y)/(5)-1)=(1)/((y-5)/(5))

Now, using division of fractions


((a)/(b))/((c)/(d))=((a)(d))/((b)(c))

So, that is:


((1)/(1))/((y-5)/(5))=((1)(5))/((1)(y-5))=(5)/(y-5)

User Julio Villane
by
5.9k points